2019
DOI: 10.1111/jcpe.13091
|View full text |Cite
|
Sign up to set email alerts
|

Association between central obesity and tooth loss in the non‐obese people: Results from the continuous National Health and Nutrition Examination Survey (NHANES) 1999–2012

Abstract: Objectives This study was to investigate the association between central obesity and tooth loss in non‐obese population. Material and Methods This national cross‐sectional study included 19436 participants, aged 19–74 years with body mass index(BMI) 18.5–29.9 kg/m2, from the National Health and Nutrition Examination Survey(NHANES) 1999–2012. Tooth loss was measured by the number of teeth missing. Central obesity was defined by a categorized 3‐level waist circumference according to the WHO recommendation. A zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…However, these latter are frequently processed foods that are high in fat and sugar and with a poor content of vitamins and minerals, leading to fat deposition, oxidative stress, inflammation, and, consequently, increased risk of cardiovascular disease and metabolic syndrome [88,[95][96][97]. In fact, it is well established that obesity leads to chronic low-grade inflammation, increasing the susceptibility to dental caries, periodontal disease, and tooth loss [98]. The excess of energy is stored in adipocytes and leads to both hypertrophy and hyperplasia, resulting in an abnormal adipocyte function.…”
Section: Impact Of Oral Health On Nutritional Statusmentioning
confidence: 99%
“…However, these latter are frequently processed foods that are high in fat and sugar and with a poor content of vitamins and minerals, leading to fat deposition, oxidative stress, inflammation, and, consequently, increased risk of cardiovascular disease and metabolic syndrome [88,[95][96][97]. In fact, it is well established that obesity leads to chronic low-grade inflammation, increasing the susceptibility to dental caries, periodontal disease, and tooth loss [98]. The excess of energy is stored in adipocytes and leads to both hypertrophy and hyperplasia, resulting in an abnormal adipocyte function.…”
Section: Impact Of Oral Health On Nutritional Statusmentioning
confidence: 99%
“…Obesity has also been directly associated with tooth loss. However, the great majority of studies on this association are cross‐sectional (Jiang et al 2013; Jung et al 2011; Kang et al 2019; Ojima et al 2007; Pilotto et al 2014), and some have evaluated self‐reported tooth loss (Bernardo Cde et al 2012; Ostberg et al 2009). A systematic review (Nascimento et al 2016) included only four cross‐sectional studies and found that the chances for tooth loss increased by 49% in obese compared to normal‐weight individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, periodontitis has been associated as a potential risk for increased morbidity for systemic conditions including diabetes mellitus, rheumatoid arthritis, obesity, osteoporosis and adverse pregnancy events (Bartold and Lopez-Oliva, 2000;Papapanou, 2015;Penoni et al, 2017;Sanz et al, 2018;Kang et al, 2019). The bidirectional relationship between diabetes mellitus and periodontitis has been extensively investigated and demonstrates that control of one disease positively impacts the other (Sima and Glogauer, 2013).…”
Section: Interrelationship With Systemic Conditionsmentioning
confidence: 99%